PERJANJIAN JUAL BELI TANAH YANG TIDAK DILAKUKAN DIHADAPAN PEJABAT PEMBUAT AKTA TANAH - Besiroh (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Problems that occur in the legal activities of buying and selling land often arise from negligence on the part of the seller or buyer. Under the pretext of speeding up administrative matters, it can lead to fatal errors. This case can occur when the sale and purchase of land is not carried out in the presence of the Land Deed Official (PPAT). The aim of this research is to find out the legality of land sales and purchases carried out not in the presence of the PPAT and the position of agreements regarding land sales and purchases carried out not in the presence of land deed making officials (PPAT) using normative legal research methods. Land sale and purchase agreements that are not executed in the presence of a land deed-making official are an important concern in the field of civil law. The purpose of this article is to analyze all legal aspects relevant to land sale and purchase agreements that are not executed in the presence of a land deed official. The juridical review was carried out based on analytical research using literature studies, as well as secondary data obtained from literature, PUU, and Regional Autonomy regulations. In the end, research shows that land sale and purchase agreements that are not executed in the presence of a land deed-making official can still be accepted, provided that the sale and purchase agreement meets the applicable juridical requirements.